Language and Law / Linguagem e Direito: Complete Issue - Soltan, Angela; Rousi, Rebekah; Rosendo, Lucía Ruiz (Language and Law / Linguagem e Direito, 2026)
Language, Law and Rights: Balancing AI-Driven Technology and Equity